Sustainable Development of Small-Scale Fisheries and the Need for Strong Measures to Protect Small-Scale Fisheries in International Trade Law - Auld, Kathleen Gwynneth (Department of Public Law, 2021)
The small-scale fisheries sector makes a valuable contribution to livelihoods and food security, particularly in under-resourced countries. Yet small-scale fishers and fishing communities are often vulnerable and marginalised, and the small-scale sector is largely ignored by governments providing subsidies to their fishing industries. Provisions seeking to ban harmful fisheries subsidies are now the subject of several large international trade agreements and negotiations. While this is a laudable and necessary goal, the binding nature and robust enforcement mechanisms of trade agreements make it imperative that small-scale fisheries are protected and provided for in these agreements in the interests of sustainable development and poverty reduction. The thesis considers how this can be achieved. In order to determine what would best serve the interests of small-scale fisheries in trade agreements, the thesis creates a framework of development needs, which underpins the analysis in the remainder of the thesis. This analysis revolves around three large trade agreements and negotiations containing provisions on fisheries subsidies – namely the World Trade Organization (WTO) negotiations, the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP), and the United States-Mexico-Canada Agreement (USMCA). Drawing on the development framework, the thesis identifies a number of shortcomings in these agreements when it comes to protections for small-scale fisheries, including a lack of provision for important development needs and a failure to achieve an appropriate balance between development and sustainability considerations. The thesis also considers potential problems that could arise in the conclusion and enforcement of trade agreements dealing with fisheries subsidies, particularly as these relate to small-scale fisheries and sustainable development. Based on this analysis, the thesis makes a number of recommendations to be incorporated in trade agreements going forward that would adequately protect and promote the interests of small-scale fisheries, while not losing sight of sustainability concerns and the practical realities of negotiating complex international trade agreements. These include, inter alia, exemptions for important social assistance subsidies, better representation and transparency, and measures to improve equity between the small-scale sector and other fishing sectors.